2008
DOI: 10.1111/j.1468-0432.2008.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm Home for the Kids’: Contradictory Implications for Work–Life Balance of Teleworking Mothers

Abstract: This study explores the experience of time flexibility and its relationship to work-life balance among married female teleworkers with school-aged children. Drawing from a larger study of teleworkers from a Canadian financial corporation, 18 mothers employed in professional positions discussed work, leisure and their perceptions of work-life balance in in-depth interviews. Telework was viewed positively because flexible scheduling facilitated optimal time management. A key factor was the pervasiveness of careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
265
2
23

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(304 citation statements)
references
References 23 publications
14
265
2
23
Order By: Relevance
“…In fact, a study by the General Services Administration (GSA, 2006) reported that the financial benefit a company accrues by allowing its employees to telecommute far outstrips the cost to the company of providing the necessary telecommuting products and services (see also Robert and Borjesson, 2006). At the same time, potential benefits of telecommuting to employees include work schedule flexibility, reduced transportation costs, lower overall commuting stress levels, improved job satisfaction, and improved work-family life balance (Madsen, 2003, Potter, 2003, Gajendran and Harrison, 2007, Hilbrecht et al, 2008, and Fonner and Roloff, 2010. Thus, instituting telecommuting programs may not only enable planning organizations to reduce traffic congestion/GHG emissions, but also may provide tangible benefits to employers and employees.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In fact, a study by the General Services Administration (GSA, 2006) reported that the financial benefit a company accrues by allowing its employees to telecommute far outstrips the cost to the company of providing the necessary telecommuting products and services (see also Robert and Borjesson, 2006). At the same time, potential benefits of telecommuting to employees include work schedule flexibility, reduced transportation costs, lower overall commuting stress levels, improved job satisfaction, and improved work-family life balance (Madsen, 2003, Potter, 2003, Gajendran and Harrison, 2007, Hilbrecht et al, 2008, and Fonner and Roloff, 2010. Thus, instituting telecommuting programs may not only enable planning organizations to reduce traffic congestion/GHG emissions, but also may provide tangible benefits to employers and employees.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Some of the factors that have been shown to have a positive relationship with work-life balance. These factors include job satisfaction (Saif, Malik, & Awan, 2010); and telework (Felstead, Jewson, Phizaklea, & Walters, 2002;Morganson, Major, Oborn, Verine, & Heelan, 2010;Hilbrecht, Shaw, Johnson, & Andrey, 2008). On the other hand, some factors were found to have a negative impact on work-life balance, for example work overload (Virick, Lilly, & Casper, 2007), and job demands (Chiang, Birtch, & Kwan, 2010).…”
Section: The Balance Theory and Work-life Balancementioning
confidence: 99%
“…Social media -for example -can facilitate greater communication between parents and an adolescent's peers, including through profile monitoring practices (such as snooping). Media and technology also serve as exosystems that influence microsystems and mesosystems, such as the way in which mobile technologies have impacted upon parents' working patterns allowing more opportunity to work from home and thus potentially impacting upon the nature of the adolescent-parent relationship (Hilbrecht, Shaw, Johnson, & Andrey, 2008). Lastly, media and technology may also be seen as part of the macrosystem shaping cultural norms and values.…”
Section: Contextualising Developmentmentioning
confidence: 99%